THE USE OF WHIPPLE OPERATION IN PATIENTS WITH COMPLICATED FORMS OF CHRONIC PANCREATITIS - Pylypchuk, V.I. (World of Medicine and Biology, 2018)
During the period of 2011-2017, 170 patients with complicated forms of CP were operated on in the Department of General Surgery of the Ivano-Frankivsk Regional Clinical Hospital. In 11 out of 170 patients (6.5%) the method of the surgical choice was the Whipple operation (the main group). The immediate and long-term outcomes of this operation were compared with the similar results in 61 out of 170 patients (35.9%) who were applied duodenum-saving resection operations (the comparison group). In patients with CP, in whom it was impossible to exclude malignant process in the pancreatic head, the Whipple operation should be considered as the operation of choice. The analysis of the immediate and long-term outcomes of the Whipple operation in patients with complicated forms of CP shows that this intervention is effective, gives a stable clinical effect. Patients undergoing pancreatic-duodenal resection because of CP, the level of early postoperative complications, long-term consequences and life quality indicators do not significantly differ from similar figures after duodenum-preserving surgical interventions.